The Application of Memorization and Play Methods to Increase Children's Interest in Learning at TPQ Bahrul Ulum - Ardiyansyah, Alizhar Tri; Murtiani, Rifqi; Rohmana, Wahyu Indah Mala (Jurnal Masyarakat Religius dan Berwawasan, 2024)
This research aims to examine the interest of children at the Bahrul Ulum Quran Education Park (TPQ) in learning using the memorization and play method. With the title "The Interest of TPQ Bahrul Ulum Children Using the Memorization and Play Method."The research method used is an experiment with a pre-post test design and a control group.Learning with the memorization and play method was implemented in the experimental group, while the control group received conventional learning. Data were collected through observation to assess the level of children's interest in learning. The research results show that the children of TPQ Bahrul Ulum exhibit a higher level of interest in learning using the memorization and play method compared to conventional learning. The conclusion of this research is that the memorization and play method is effective in increasing the interest of TPQ children in learning. Recommendations for future learning activities involve the broader application of this method, with an emphasis on creative and interactive aspects. This research contributes to a deeper understanding of learning approaches that can enrich the learning experiences of children in TPQ, supporting the development of the quality of religious education in that environment.